Efficient Secure Two-Party Computation with Untrusted Hardware Tokens - Järvinen, Kimmo; Kolesnikov, Vladimir; Sadeghi, Ahmad-Reza; Schneider, Thomas (Towards Hardware-Intrinsic Security, 2010)
Secure and efficient evaluation of arbitrary functions on private inputs has been subject of cryptographic research for decades. In particular, the following scenario appears in a variety of practical applications: a service provider (server $$\mathcal{S}$$ ) and user (client $$\mathcal{C}$$ ) wish to compute a function f on their respective private data, without incurring the expense of a trusted third party. This can be solved interactively using Secure Function Evaluation (SFE) protocols, for example, using the very efficient garbled circuit (GC) approach [23, 36]. However, GC protocols potentially require a large amount of data to be transferred between $$\mathcal{S}$$ and $$\mathcal{C}$$ . This is because f needs to be encrypted (garbled) as $$\widetilde{f}$$ and transferred from $$\mathcal{S}$$ to $$\mathcal{C}$$ .